in Search of Address Terms in Novel - Ahmad Tauchid (Loquen, 2018)
Abstract: Language has an important role in human life, basically as a means of communication. Language is primarily an instrument of communication among human being in community. People use language as a means of communication to build relationship among human being and to express their feeling, ideas, and knowledge, a process where people are involved in interaction. That is why sociolinguistics deals with the inter relationship between language and society. Based on the background of the problem stated above, the writer would like to propose the problems as follows: What kinds of address terms are used by the characters in novel The Secret Island by Enid Blyton?; How are those address terms used by the character in novel The Secret Island by Enid Blyton? In conducting this study, the writer uses qualitative method. From the analysis, the writer can find that the characters use three kinds of address terms there are first name (FN), title plus last name (TLN), and kinship terms (KT). They use the address terms based on their relationship and it can describing as follows: They use first name (FN) when their relationship is very close or intimate, such as close friend, siblings, etc; They use title plus last name (TLN) when their relationship is not so very close or people older than them, such as aunt Harriet, uncle Henry, etc; They use kinship terms (KT) when their relationship is family very close or intimate, such as dad, mummy, father, mother, aunt, uncle, etc.